Hedging and pricing in imperfect markets under non-convexity - Hirbod Assa; Nikolay Gospodinov (Federal Reserve Bank of Atlanta, 2014)
This paper proposes a robust approach to hedging and pricing in the presence of market imperfections such as market incompleteness and frictions. The generality of this framework allows us to conduct an in-depth theoretical analysis of hedging strategies for a wide family of risk measures and pricing rules, which are possibly non-convex. The practical implications of our proposed theoretical approach are illustrated with an application on hedging economic risk.
Keywords: G11; G13; C22; E44; 330; imperfect markets; risk measures; hedging; pricing rule; quantile regression